2020
DOI: 10.1021/acs.jpcc.0c02045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HPHT Processing on Structural and Thermoelectric Properties of Low-Cost Type-I Clathrate Ba8Cu6Si40

Abstract: Si-based clathrate thermoelectric (TE) materials composed of low-cost, nontoxic, lightweight, and earth-abundant elements are typical representatives of cheaper thermoelectric materials. However, synthesis is difficult, and the relatively low ZT values are the barriers hindering the further development of the silicon clathrates. So, it is necessary to explore an alternative synthetic method and improve the ZT values simultaneously. In this work, Si-based clathrate Ba8Cu6Si40 samples have been synthesized by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Such a high density of grain boundaries should be attributed to the HPHT synthesis method. Previous work has confirmed that the HPHT method could generate nanograins and observably suppress grain growth in multiple thermoelectric systems, including Bi 2 Te 3 -, CoSb 3 -, and Ba 8 Si 46 -based systems, thus enhancing the density of grain boundaries. Figure B shows a close-up of the grain boundary area, exhibiting an incoherent nature that should consist of geometrical necessary dislocations. The corresponding fast Fourier transform (FFT) analyses and atomic models for the upper and bottom grains (Figure B) are illustrated in Figure C1,C2, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…Such a high density of grain boundaries should be attributed to the HPHT synthesis method. Previous work has confirmed that the HPHT method could generate nanograins and observably suppress grain growth in multiple thermoelectric systems, including Bi 2 Te 3 -, CoSb 3 -, and Ba 8 Si 46 -based systems, thus enhancing the density of grain boundaries. Figure B shows a close-up of the grain boundary area, exhibiting an incoherent nature that should consist of geometrical necessary dislocations. The corresponding fast Fourier transform (FFT) analyses and atomic models for the upper and bottom grains (Figure B) are illustrated in Figure C1,C2, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…Until now, synergistically regulating carrier and phonon transport on the same scale is extremely difficult for all TE materials without cage structures. For those TE materials with cage structures such as skutterudite and clathrate, one can use different atoms to fill the cages to optimize the band structure and to provide scattering centers for phonon, realizing simultaneous regulation of carrier and phonon transport on the atomic scale [3][4][5][6]. However, for all other TE materials, one can only separately tune electric transport properties by band engineering on the atomic scale [7][8][9][10], and/or thermal transport properties by phonon engineering on the nanoscale [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The ordered arrangement has been elaborated in section 2 according to the crystal structure. In addition, Sun et al showed that implementing pressure during the synthesis process of Ba 8 Cu 6 Si 40 not only can manipulate grain sizes, but can change the surface morphology of grains (figures 5(E) and (F)) [126]. The researchers claimed that pressure-induced changes were rare happened in surface characteristics of grains, it might need to be investigated further to reveal the intrinsic mechanism of pressure modulating the surface crystallization.…”
Section: Microstructural Evolution With Pressurementioning
confidence: 99%